Strengthening research regulatory capacity in the East African community: a multi country training program on emerging and complex study designs - Mathius Amperiize; Belinda Twesigye; Beth Mutumba; Hellen Opolot; Soazic Gardais; Steve Wandiga; Helen Ndagije; Jeremiah Kidola; Vincent Mutabazi; Ramadhan Nyandwi; Lina S. Mathew; Novat Twungubumwe; et al. (BMC Medical Ethics, 2026)
Background: The East African Community (EAC) has experienced a significant increase in volume and complexity ofclinical research driven by the epidemics of emerging and re-emerging infectious diseases such as HIV, Ebola, COVID-19, and mpox. This demands for robust research, scientific, and ethical oversight. We aimed to strengthen the capacity of national research regulatory authorities (NRRA), research ethics committees (RECs), and researchers for review and oversight of studies with complex and emerging designs. Methods: We implemented a blended training program from February 2024 to February 2025 in six EAC partner states, including; republic of Burundi, republic of Kenya, republic of Rwanda, republic of South Sudan, republic of Tanzania, and republic of Uganda. Trainees were evaluated using pre and post-training assessments, and also provided qualitative responses. Results: A total of 186 participants completed the training, of which 59.0% (110/186) were males. Participants demonstrated a marked improvement in knowledge, with mean scores increasing from 52.9% at pre-test to 84.0% at post-test, and the proportion of participants that passed increased from 18.1% (34/186) at pre-test to 84.2% (157/186) at post-test. Three main themes emerged from the open-ended response evaluations: (1) enhanced understanding of emerging and complex study designs, (2) relevance to professional roles and practice, and (3) demand for advanced methodological training. Conclusions: There was a substantial shift in knowledge on emerging and complex research study designs. We recommend regular training of NRRA and REC members to improve the quality of review of research protocols with complex and emerging study designs.
Keywords: Research ethics committees; Capacity building; Emerging and complex study designs; National research regulatory authority; Researchers